Pressure-sensitive adhesive composition, pressure-sensitive adhesive film, surface protection film for polarizing plate, and optical film with pressure-sensitive adhesive layer
The adhesive composition for surface protection films, featuring a specific blend of acrylic polymers and an ionic antistatic agent, addresses the challenge of achieving balanced adhesive strength, contamination resistance, and antistatic performance across different substrates, ensuring stability and effectiveness over time.
Patent Information
- Application Number
- JP2023032055
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-03-02
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2037-09-28
AI Technical Summary
Existing adhesive compositions for surface protection films struggle to simultaneously achieve excellent adhesive strength at low and high peeling speeds, contamination resistance, and antistatic performance without degradation over time, especially when used with substrates like TAC, PMMA, and PET.
A pressure-sensitive adhesive composition containing a first acrylic polymer without polyalkylene glycol chain-containing monomers, a second acrylic polymer with polyalkylene glycol chains, an ionic antistatic agent with a melting point of 25-50°C and F7 or more fluorine atoms, and a crosslinking system including a three or more functional isocyanate compound, a crosslinking retardant, and a metal chelate crosslinking catalyst.
The adhesive composition achieves an excellent balance of adhesive strength, contamination resistance, and antistatic performance that remains stable over time, even at high speeds, and is suitable for use with various substrates including TAC, PMMA, and PET.
Smart Images

Figure 0007670744000001 
Figure 0007670744000002 
Figure 0007670744000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive composition containing an antistatic agent, and a surface protective film. More specifically, the present invention relates to a pressure-sensitive adhesive composition for a surface protective film used to protect the surface of a polarizing plate constituting a liquid crystal display by being attached to the polarizing plate, the pressure-sensitive adhesive composition having excellent adhesive performance and excellent antistatic performance without deterioration over time, and a surface protective film using the pressure-sensitive adhesive composition. [Background technology]
[0002] Conventionally, in the manufacturing process of optical members such as polarizing plates that are components of liquid crystal displays, a surface protection film is attached to temporarily protect the surface of the optical member. Such a surface protection film is used only in the process of manufacturing the optical member, and is peeled off and removed from the optical member when the optical member is assembled into a liquid crystal display. Since such a surface protection film for protecting the surface of the optical member is used only in the manufacturing process, it is also generally called a process film.
[0003] The surface protection film used in the process of manufacturing an optical component has an adhesive layer formed on one side of an optically transparent polyethylene terephthalate (PET) resin film, and a release film that has been subjected to a release treatment to protect the adhesive layer until it is attached to the optical component is attached on the adhesive layer. Furthermore, optical members such as polarizing plates, with a surface protection film attached thereto, undergo product inspections that involve optical evaluation of the display performance, hue, contrast, and presence of foreign matter of the liquid crystal display panel. For this reason, the surface protection film is required to have the performance that the pressure-sensitive adhesive layer is free of air bubbles, foreign matter, and low molecular weight components of the pressure-sensitive adhesive composition, that is, to have contamination resistance. In addition, when peeling off a surface protection film from an optical component such as a polarizing plate, there is a concern that the peeling charge generated by static electricity generated when the pressure-sensitive adhesive layer is peeled off from the adherend may affect the breakdown of the electric control circuit of the liquid crystal display, and therefore the pressure-sensitive adhesive layer is required to have excellent antistatic properties. Furthermore, in recent years, in addition to the conventional triacetyl cellulose (TAC), materials that are prone to peeling static electricity when the surface protective film of a polarizing plate is peeled off, such as acrylic resins such as polymethyl methacrylate (PMMA), polyester resins such as polyethylene terephthalate (PET), cyclic olefin polymers, polycarbonates, etc., are being increasingly used as protective layers (sometimes called protective films) for the polarizers of polarizing plates. For this reason, there is a demand for the pressure-sensitive adhesive layer for the surface protective film of a polarizing plate to have antistatic performance that is superior to that of conventional materials. Furthermore, when the surface protection film is finally peeled off from an optical member such as a polarizing plate, it is required that the film can be peeled off quickly, that is, the adhesive strength is required to change little depending on the peeling speed so that the film can be peeled off quickly even when peeled off at high speed.
[0004] Thus, in recent years, the performance requirements for the adhesive layer constituting the surface protection film have been set forth in terms of ease of use when using the surface protection film, such as (1) a balance of adhesive strength at both low and high peel speeds, (2) contamination resistance, and (3) excellent antistatic properties. However, although it is possible to satisfy each of the required performances (1) to (3) for the pressure-sensitive adhesive layer constituting the surface protection film, it has been a difficult task to simultaneously satisfy all of the required performances (1) to (3) required for the pressure-sensitive adhesive layer of the surface protection film. Furthermore, it has also been a very difficult task to form a pressure-sensitive adhesive layer of a surface protection film from the same pressure-sensitive adhesive composition that can be used for the surfaces of substrates other than TAC, which is a substrate that has been conventionally used, such as acrylic resins such as polymethyl methacrylate (PMMA), polyester resins such as polyethylene terephthalate (PET), cyclic olefin polymers, and polycarbonates, and that satisfies the required performances (1) to (3).
[0005] In order to solve such problems, for example, the following proposals are known regarding (1) balancing the adhesive strength at low and high peel speeds, (2) having stain resistance, and (3) excellent antistatic performance.
[0006] (1) Regarding balancing adhesive strength at low and high peeling speeds, an acrylic adhesive layer made of a copolymer of a (meth)acrylic acid alkyl ester having an alkyl group with 7 or less carbon atoms and a carboxyl group-containing copolymerizable compound, which is crosslinked with a crosslinking agent, has the problem that the adhesive transfers to the adherend when adhered for a long period of time, and the adhesive strength to the adherend increases significantly over time. To avoid this, a pressure-sensitive adhesive layer is known that uses a copolymer of a (meth)acrylic acid alkyl ester having an alkyl group with 8 to 10 carbon atoms and a copolymerizable compound having an alcoholic hydroxyl group, and crosslinks the copolymer with a crosslinking agent (Patent Document 1). Also proposed is a copolymer similar to the above, which is mixed with a small amount of a copolymer of an alkyl (meth)acrylate ester and a copolymerizable compound containing a carboxyl group, and is crosslinked with a crosslinking agent to provide an adhesive layer. However, when used for surface protection of a plastic plate or the like that has a low surface tension and a smooth surface, there are problems such as peeling phenomena such as lifting due to heating during processing or storage, and poor removability when peeled at high speeds, which are the range of manual work.
[0007] In order to solve these problems, a pressure-sensitive adhesive composition has been proposed in which a copolymer of a monomer mixture obtained by adding a) 100 parts by weight of a (meth)acrylic acid alkyl ester mainly composed of a (meth)acrylic acid alkyl ester having an alkyl group having 8 to 10 carbon atoms, b) 1 to 15 parts by weight of a carboxyl group-containing copolymerizable compound, and c) 3 to 100 parts by weight of a vinyl ester of an aliphatic carboxylic acid having 1 to 5 carbon atoms, is blended with a crosslinking agent in an amount equivalent to or greater than the amount of the carboxyl group in the above component b) (Patent Document 2). The adhesive composition described in Patent Document 2 does not suffer from peeling phenomena such as lifting during processing or storage, and furthermore, has a small increase in adhesive strength over time and is excellent in removability; it can be peeled off with little force even after long-term storage, particularly long-term storage under a high-temperature atmosphere, without leaving any adhesive residue on the adherend, and can be peeled off with little force even when peeled off at high speed.
[0008] Regarding (2) the stain resistance, a pressure-sensitive adhesive composition has been disclosed that contains 100 parts by mass of a (meth)acrylic copolymer having a weight average molecular weight of 100,000 or more and less than 1,000,000, which is composed of 0 part by mass or more and less than 0.5 part by mass of a carboxyl group-containing monomer, 0.6 to 9 parts by mass of a hydroxyl group-containing (meth)acrylic monomer, and 99.4 to 90.5 parts by mass of a (meth)acrylic acid ester monomer; and 0.1 to 5 parts by mass of a carbodiimide crosslinking agent (Patent Document 3). The adhesive composition described in Patent Document 3 is characterized by using a carbodiimide-based crosslinking agent as a crosslinking agent for a (meth)acrylic copolymer of a specific composition. This provides the adhesive layer with a crosslinked structure that can follow shrinkage caused by pressure and temperature during autoclave treatment. For this reason, the adhesive layer formed using the adhesive composition is capable of suppressing and preventing foaming even under high temperature and high pressure conditions (during autoclave treatment), and is said to have excellent resistance to contamination of adherends and excellent transparency.
[0009] As for (3) excellent antistatic performance, a method of kneading an antistatic agent into the base film has been suggested as a method for imparting antistatic properties to a surface protective film. Examples of the antistatic agent disclosed herein include (a) various cationic antistatic agents having a cationic group, such as a quaternary ammonium salt, a pyridinium salt, or a primary to tertiary amino group; (b) anionic antistatic agents having an anionic group, such as a sulfonate group, a sulfate group, a phosphate group, or a phosphonate group; (c) amphoteric antistatic agents, such as amino acid-based and amino sulfate-based agents; (d) nonionic antistatic agents, such as amino alcohol-based, glycerin-based, and polyethylene glycol-based agents; and (e) polymeric antistatic agents obtained by increasing the molecular weight of the above-mentioned antistatic agents (Patent Document 4). In recent years, it has been proposed to incorporate such antistatic agents into the base film, or to incorporate the agent directly into the pressure-sensitive adhesive layer, rather than coating the surface of the base film.
[0010] Also disclosed is an antistatic adhesive composition in which a salt having an anion having a fluoro group and a sulfonyl group is dispersed, the salt having an anion having a fluoro group and a sulfonyl group being dispersed in a dissolved state in a polyether ester plasticizer containing a polyether group in the main chain (Patent Document 5). The adhesive composition described in Patent Document 5 discloses the use of a plasticizer consisting of an ester formed from a mono- or dicarboxylic acid having a saturated or unsaturated acyclic hydrocarbon group and an alcohol having a C1-20 acyclic hydrocarbon group, or an ester in which the unsaturated group in the unsaturated acyclic hydrocarbon group has been epoxidized. Such a mono- or dicarboxylic acid having a saturated or unsaturated acyclic hydrocarbon group has a carbon number close to that of the acrylic monomer constituting the acrylic copolymer used in the adhesive layer, and thus has good compatibility with the antistatic adhesive composition, and the plasticizer is suitably retained in the acrylic antistatic adhesive composition, thereby suppressing bleed-out. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Japanese Patent Application Publication No. 63-225677 [Patent Document 2] Japanese Patent Application Publication No. 11-256111 [Patent Document 3] JP 2011-122054 A [Patent Document 4] Japanese Patent Application Publication No. 11-070629 [Patent Document 5] JP 2014-118469 A Summary of the Invention [Problem to be solved by the invention]
[0012] Thus, in the prior art, the required performance of the adhesive layer constituting the surface protection film has been a balance of adhesive strength at low and high peel speeds, contamination resistance, excellent antistatic performance, etc., but while it has been possible to satisfy each of these individual required performances, it has not been possible to simultaneously satisfy all of the required performances required of the adhesive layer of a surface protection film. Furthermore, in the prior art, it was not possible to produce a pressure-sensitive adhesive layer that could be used with all surface substrates consisting of TAC, PMMA, and PET and that simultaneously satisfied all of the required performance requirements for a pressure-sensitive adhesive layer of a surface protection film.
[0013] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a pressure-sensitive adhesive composition and a surface protection film which can form, from the same pressure-sensitive adhesive composition, a pressure-sensitive adhesive layer that has an excellent balance of adhesive strength at both low and high peel speeds, and further has contamination resistance and excellent adhesive performance, and further is usable with surface substrates made of TAC, PMMA, and PET, does not deteriorate over time, and has excellent antistatic performance. [Means for solving the problem]
[0014] In pressure-sensitive adhesive compositions with antistatic properties and surface protection films using the same, there is a trade-off between the antistatic properties and the contamination resistance of an adherend, and it has been extremely difficult to improve the contamination resistance while maintaining the antistatic properties. Therefore, the inventors of the present invention have been able to solve this problem by defining as the technical concept of the present invention a pressure-sensitive adhesive composition comprising a first acrylic polymer which does not contain a polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer and is copolymerized with a copolymerizable monomer containing a carboxyl group, a second acrylic polymer which contains a polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer, and an antistatic agent preferably consisting of a polyether-containing silicone compound and an ionic compound having a melting point of 25°C or higher and having an anion having the number of fluorine atoms of F7 or more (e.g., nonafluorobutanesulfonate anion).
[0015] In order to solve the above problems, the present invention provides a pressure-sensitive adhesive composition comprising an acrylic polymer, an antistatic agent, and a crosslinking agent, the acrylic polymer being the following first acrylic polymer and second acrylic polymer: The first acrylic polymer is (A) at least one (meth)acrylic acid ester monomer having an alkyl group carbon number of C1 to C18, relative to a total of 100 parts by weight (B) 1.0 to 6.0 parts by weight of at least one copolymerizable monomer containing a hydroxyl group; (C) 0.01 to 0.6 parts by weight of at least one copolymerizable monomer containing a carboxyl group; a first acrylic polymer which is a copolymer having an acid value of 0.1 to 1.0 and a weight average molecular weight of more than 300,000 and not more than 1,200,000, obtained by copolymerizing the above without containing a polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer; the first acrylic polymer contains 70 parts by weight or more of 2-ethylhexyl acrylate out of a total of 100 parts by weight of the at least one (meth)acrylic acid ester monomer (A) having an alkyl group with a carbon number of C1 to C18; The second acrylic polymer is (a) at least one (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C18; (b) at least one copolymerizable monomer containing a hydroxyl group; (c) at least one polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer; a second acrylic polymer having a weight average molecular weight of more than 300,000 and not more than 800,000; the (c) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer has an average repeat number of alkylene oxides constituting the polyalkylene glycol chain of 3 to 14; the (c) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer has a diester content of 0.2% or less, the first acrylic polymer and the second acrylic polymer have a glass transition temperature of 0° C. or lower; the crosslinking agent is (D) a tri- or higher functional isocyanate compound, the antistatic agent is (G) an ionic compound having a melting point of 25 to 50°C, which is composed of a cation and an anion and has an anion in which the number of fluorine atoms is F7 or more; The present invention provides a pressure-sensitive adhesive composition, characterized in that the pressure-sensitive adhesive composition further comprises (E) a crosslinking retarder, and (F) a crosslinking catalyst other than a tin compound.
[0016] The pressure-sensitive adhesive composition of the present invention is a pressure-sensitive adhesive composition for a surface protection film to be bonded to a protective layer of a polarizer of a polarizing plate, and it is preferable that the protective layer of the polarizer of the polarizing plate is one type selected from the group consisting of a TAC-based film, a PMMA-based film, and a PET-based film, and that the surface treatment applied to the surface of the protective layer of the polarizer of the polarizing plate is one type selected from the group consisting of untreated, AG treatment, LR treatment, AR treatment, AG-LR treatment, and AG-AR treatment.
[0017] The anion of the ionic compound is C6F5(CF2) n COO - , C6F5(CF2) n SO3 - , C6F5(CF2) n O - , C6F5O(CF2) n SO3 - , (C6F5CO)2N - , (C6F5CO)3C - , (C6F5SO2)2N - , (C6F5SO2)3C - , (C6F5OSO2)2N - , (C6F5OSO2)3C - , (C6F5)4B - , CF3(CF2)3SO3 - and preferably contains, as an anion, at least one selected from the group consisting of the following, and the ionic compound is contained in a ratio of 0.01 to 15 parts by weight per 100 parts by weight of the first acrylic polymer.
[0018] It is preferable that the cation of the ionic compound is one selected from the group consisting of pyridinium, imidazolium, phosphonium, sulfonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylium, lithium, and morpholinium, and that the ionic compound is contained in a ratio of 0.01 to 15 parts by weight per 100 parts by weight of the first acrylic polymer.
[0019] The pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition has a surface resistivity of 1.0×10 +12 It is preferable that the peel charging voltage of the pressure-sensitive adhesive layer against a low refractive index layer formed using a composition for forming a low refractive index layer containing a fluorine compound on the adhesion surface is within the range of -0.3 to +0.3 kV, and the adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition has an adhesive strength of 0.04 to 0.2 N / 25 mm at a low peel speed of 0.3 m / min and an adhesive strength of 2.0 N / 25 mm or less at a high peel speed of 30 m / min.
[0020] The (B) hydroxyl group-containing copolymerizable monomer of the first acrylic polymer and the (b) hydroxyl group-containing copolymerizable monomer of the second acrylic polymer are at least one selected from the group consisting of 8-hydroxyoctyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide, and the (C) carboxyl group-containing copolymerizable monomer is at least one selected from the group consisting of 8-hydroxyoctyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide. The polymerizable monomer is preferably at least one selected from the group consisting of (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl maleic acid, carboxypolycaprolactone mono(meth)acrylate, and 2-(meth)acryloyloxyethyl tetrahydrophthalic acid.
[0021] It is preferable that the (E) crosslinking retarder is a keto-enol tautomer compound, and the (E) crosslinking retarder is contained in a ratio of 0.1 to 300 parts by weight relative to 100 parts by weight of the first acrylic polymer, the (F) crosslinking catalyst is at least one metal chelate compound selected from the group consisting of aluminum chelate compounds, titanium chelate compounds, and iron chelate compounds, and the (F) crosslinking catalyst is contained in a ratio of 0.001 to 0.5 parts by weight relative to 100 parts by weight of the first acrylic polymer, and the (E) / (F) weight ratio is 80 to 1000.
[0022] The pressure-sensitive adhesive composition preferably contains 0.01 to 0.5 parts by weight of a polyether-modified siloxane compound having an HLB value of 6 to 12 and a weight average molecular weight of 10,000 or less, based on 100 parts by weight of the first acrylic polymer.
[0023] The pressure-sensitive adhesive composition contains 0.1 to 5.0 parts by weight of the second acrylic polymer relative to 100 parts by weight of the first acrylic polymer, and the second acrylic polymer is preferably a copolymer obtained by copolymerizing 2.0 to 12.0 parts by weight of at least one or more copolymerizable monomers containing a hydroxyl group and 1 to 30 parts by weight of at least one or more mono(meth)acrylic acid ester monomers containing a polyalkylene glycol chain, relative to 100 parts by weight of at least one or more (meth)acrylic acid ester monomers having a carbon number of C1 to C18 in the alkyl group. The weight-average molecular weight of the copolymer is preferably more than 300,000 and 1,000,000 or less, and more preferably more than 300,000 and 800,000 or less. In addition, it is preferable that the ratio K=β2 / β1 of the total parts by weight β1=100×(B) / (A) of the at least one or more copolymerizable monomers containing a hydroxyl group (B) to a total of 100 parts by weight of the at least one or more (meth)acrylic acid ester monomers having a carbon number of C1 to C18 in the alkyl group (A) of the first acrylic polymer and the total parts by weight β2=100×(b) / (a) of the at least one or more copolymerizable monomers containing a hydroxyl group (b) to a total of 100 parts by weight of the at least one or more (meth)acrylic acid ester monomers having a carbon number of C1 to C18 in the alkyl group (a) of the second acrylic polymer is within the range of 1.0 to 2.0.
[0024] The second acrylic polymer is a copolymer having a weight average molecular weight of more than 300,000 and not more than 800,000, the polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer has an average repeat number of alkylene oxide constituting the polyalkylene glycol chain of 3 to 14, the polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer has a diester content of 0.2% or less, and the polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer is at least one selected from the group consisting of polyalkylene glycol mono(meth)acrylate, methoxypolyalkylene glycol (meth)acrylate, and ethoxypolyalkylene glycol (meth)acrylate, preferably in an amount of 1 to 50 parts by weight, more preferably 1 to 40 parts by weight, and particularly preferably 1 to 30 parts by weight, per 100 parts by weight of the second acrylic polymer.
[0025] The present invention also provides a pressure-sensitive adhesive film, comprising a resin film and a pressure-sensitive adhesive layer formed by crosslinking the pressure-sensitive adhesive composition laminated on one side of the resin film.
[0026] The present invention also provides a surface protection film using the above-mentioned pressure-sensitive adhesive film.
[0027] The present invention also provides a surface protection film for a polarizing plate, which uses the above-mentioned pressure-sensitive adhesive film.
[0028] The present invention also provides an optical film with a pressure-sensitive adhesive layer, comprising an optical film and a pressure-sensitive adhesive layer formed by crosslinking the pressure-sensitive adhesive composition, laminated on at least one surface of the optical film.
[0029] The present invention also provides a pressure-sensitive adhesive film, wherein one surface of the resin film opposite the surface on which the pressure-sensitive adhesive layer is formed is subjected to an antistatic treatment and an antifouling treatment. Effect of the Invention
[0030] According to the present invention, it is possible to provide a pressure-sensitive adhesive composition and a surface protection film which can form, from the same pressure-sensitive adhesive composition, a pressure-sensitive adhesive layer that has an excellent balance of adhesive strength at both low and high peel speeds, and further has contamination resistance and excellent adhesive performance, and further is usable with surface substrates made of TAC, PMMA, or PET, does not deteriorate over time, and has excellent antistatic performance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] Hereinafter, the present invention will be described based on preferred embodiments. The pressure-sensitive adhesive composition of the present embodiment is a pressure-sensitive adhesive composition containing an acrylic polymer, an antistatic agent, and a crosslinking agent, wherein the acrylic polymer is the following first acrylic polymer and second acrylic polymer: The first acrylic polymer is (A) at least one (meth)acrylic acid ester monomer having an alkyl group carbon number of C1 to C18, relative to a total of 100 parts by weight (B) 1.0 to 6.0 parts by weight of at least one copolymerizable monomer containing a hydroxyl group; (C) 0.01 to 0.6 parts by weight of at least one copolymerizable monomer containing a carboxyl group; a first acrylic polymer which is a copolymer having an acid value of 0.1 to 1.0 and a weight average molecular weight of more than 300,000 and not more than 1,200,000, obtained by copolymerizing the above without containing a polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer; the first acrylic polymer contains 70 parts by weight or more of 2-ethylhexyl acrylate out of a total of 100 parts by weight of the at least one (meth)acrylic acid ester monomer (A) having an alkyl group with a carbon number of C1 to C18; The second acrylic polymer is (a) at least one (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C18; (b) at least one copolymerizable monomer containing a hydroxyl group; (c) at least one polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer; and a second acrylic polymer, the first acrylic polymer and the second acrylic polymer have a glass transition temperature of 0° C. or lower; the crosslinking agent is (D) a tri- or higher functional isocyanate compound, the antistatic agent is (G) an ionic compound having a melting point of 25 to 50°C, which is composed of a cation and an anion and has an anion in which the number of fluorine atoms is F7 or more; The pressure-sensitive adhesive composition further comprises (E) a crosslinking retarder, and (F) a crosslinking catalyst other than a tin compound.
[0032] The pressure-sensitive adhesive composition according to this embodiment has superior adhesive performance and superior antistatic performance during peeling without deterioration over time, as compared with conventional pressure-sensitive adhesive compositions for surface protection films. In particular, when an adherend such as an optical film has an anti-fouling layer containing a fluorine compound, or a low refractive index layer formed using a composition for forming a low refractive index layer containing a fluorine compound, laminated on the surface of the adherend such as an optical film, the surface protective film of this embodiment has superior adhesion performance and excellent peel-off antistatic performance without deterioration over time, compared to surface protective films made by conventional technology, and is significantly effective in achieving both antistatic performance and contamination resistance. In other words, the adhesive composition of this embodiment and the surface protection film using the same have excellent adhesive performance and excellent antistatic performance against peeling without deterioration over time, and therefore have extremely high industrial utility.
[0033] The acrylic polymer used in the pressure-sensitive adhesive composition of the present embodiment is a main polymer of the pressure-sensitive adhesive composition, and has a glass transition temperature of 0° C. or lower. The acrylic polymer is preferably a copolymer mainly composed of (A) a (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C18.
[0034] The acrylic polymers used in the pressure-sensitive adhesive composition of the present embodiment are a first acrylic polymer that does not contain a polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer, and a second acrylic polymer that contains a polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer.
[0035] The first acrylic polymer is a copolymer having a glass transition temperature of 0° C. or lower, obtained by copolymerizing (A) a (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C18, (B) a copolymerizable monomer containing a hydroxyl group, and (C) a copolymerizable monomer containing a carboxyl group, without containing a polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer. The second acrylic polymer is a copolymer having a glass transition temperature of 0° C. or lower, obtained by copolymerizing (a) at least one (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C18, (b) at least one copolymerizable monomer containing a hydroxyl group, and (c) at least one mono(meth)acrylic acid ester monomer containing a polyalkylene glycol chain.
[0036] Examples of the (A) (meth)acrylic acid ester monomer in which the alkyl group of the first acrylic polymer has a carbon number of C1 to C18 and the (a) (meth)acrylic acid ester monomer in which the alkyl group of the second acrylic polymer has a carbon number of C1 to C18 include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, ) acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, etc. The alkyl group of the alkyl (meth)acrylate monomer may be linear, branched, or cyclic.
[0037] The first acrylic polymer used in the pressure-sensitive adhesive composition of this embodiment preferably contains 70 parts by weight or more of 2-ethylhexyl acrylate out of a total of 100 parts by weight of at least one (A) (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C18.
[0038] The first acrylic polymer used in the pressure-sensitive adhesive composition of the present embodiment contains (B) a copolymerizable monomer containing a hydroxyl group. The second acrylic polymer contains (b) a copolymerizable monomer containing a hydroxyl group. The (B) copolymerizable monomer containing a hydroxyl group of the first acrylic polymer and the (b) copolymerizable monomer containing a hydroxyl group of the second acrylic polymer are preferably at least one selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, and the like.
[0039] The first acrylic polymer preferably contains 1.0 to 6.0 parts by weight, more preferably 1.6 to 5.8 parts by weight, and particularly preferably 2.1 to 5.8 parts by weight of (B) at least one or more copolymerizable monomers containing a hydroxyl group, relative to 100 parts by weight of (A) at least one or more (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C18.
[0040] The second acrylic polymer preferably contains 2.0 to 12.0 parts by weight, more preferably 3.0 to 11.0 parts by weight, and particularly preferably 4.0 to 10.0 parts by weight of (b) at least one or more copolymerizable monomers containing a hydroxyl group, per 100 parts by weight of (a) at least one or more (meth)acrylic acid ester monomers having an alkyl group carbon number of C1 to C18.
[0041] In the first acrylic polymer, the total weight parts β1 of at least one copolymerizable monomer containing a hydroxyl group (B) is expressed by β1=100×(B) / (A) relative to a total of 100 parts by weight of at least one (meth)acrylic acid ester monomer (A) whose alkyl group has a carbon number of C1 to C18. Similarly, the total weight parts β2 of at least one copolymerizable monomer containing a hydroxyl group (b) in the second acrylic polymer is expressed by β2=100×(b) / (a) relative to a total of 100 parts by weight of at least one (meth)acrylic acid ester monomer (a) whose alkyl group has a carbon number of C1 to C18. The weight parts β2 of (b) in the second acrylic polymer are preferably equal to or greater than the weight parts β1 of (B) in the first acrylic polymer, and the ratio K=β2 / β1 is preferably within the range of 1.0 to 2.0.
[0042] The first acrylic polymer used in the pressure-sensitive adhesive composition of the present embodiment contains (C) a copolymerizable monomer containing a carboxyl group. The (C) copolymerizable monomer containing a carboxyl group is preferably at least one selected from the group consisting of (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl maleic acid, carboxypolycaprolactone mono(meth)acrylate, and 2-(meth)acryloyloxyethyl tetrahydrophthalic acid.
[0043] The first acrylic polymer preferably contains 0.01 to 0.6 parts by weight, more preferably 0.01 to 0.5 parts by weight, and particularly preferably 0.01 to 0.4 parts by weight of at least one or more copolymerizable monomers containing a carboxyl group (C) per 100 parts by weight of at least one or more (meth)acrylic acid ester monomers (A) having an alkyl group with a carbon number of C1 to C18.
[0044] The second acrylic polymer used in the pressure-sensitive adhesive composition of the present embodiment contains (c) a polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer. Therefore, in the pressure-sensitive adhesive composition of the present embodiment, the second acrylic polymer containing (c) a polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer is considered to function as an antistatic auxiliary. The second acrylic polymer is preferably contained in a ratio of 0.1 to 5.0 parts by weight, more preferably 0.1 to 3.5 parts by weight, and particularly preferably 0.1 to 2.5 parts by weight, relative to 100 parts by weight of the first acrylic polymer. If the content of the second acrylic polymer is less than the above range, the surface resistivity and peeling electrification voltage become high, the antistatic performance deteriorates, and the stain resistance of the polarizing plate deteriorates.
[0045] The (c) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer may be a compound in which one of the multiple hydroxyl groups of a polyalkylene glycol is esterified as a (meth)acrylic acid ester. Since the (meth)acrylic acid ester group is a polymerizable group, it can be copolymerized with a second acrylic polymer. It may be a polyalkylene glycol mono(meth)acrylate in which the other hydroxyl group remains OH, or an alkoxy polyalkylene glycol mono(meth)acrylate in which the other hydroxyl group is converted to an alkyl ether. Since polyalkylene glycol mono(meth)acrylate corresponds to (c), it is not classified as (B) or (b) even if it contains a hydroxyl group.
[0046] The polyalkylene glycol constituting the polyalkylene glycol chain may be any glycol compound having one or more alkylene groups, and examples thereof include polyethylene glycol, polypropylene glycol, polybutylene glycol, polyethylene glycol-polypropylene glycol, polyethylene glycol-polybutylene glycol, polypropylene glycol-polybutylene glycol, and polyethylene glycol-polypropylene glycol-polybutylene glycol.
[0047] It is preferable that (c) the polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer has an average repeat number of alkylene oxide constituting the polyalkylene glycol chain of 3 to 14. The "average repeat number of alkylene oxide" refers to the average number of repeating alkylene oxide units in the "polyalkylene glycol chain" portion contained in the molecular structure of (c) the polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer.
[0048] The diester content in the (c) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer is preferably 0.2% or less. The "diester content in the monomer" refers to the content (wt%) of polyalkylene glycol di(meth)acrylic acid ester contained in the (c) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer.
[0049] The (c) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer is preferably at least one selected from the group consisting of polyalkylene glycol mono(meth)acrylate, methoxy polyalkylene glycol (meth)acrylate, and ethoxy polyalkylene glycol (meth)acrylate. The proportion of the (c) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer in the second acrylic polymer is preferably 1 to 50 parts by weight, more preferably 2 to 35 parts by weight, and particularly preferably 2 to 25 parts by weight, per 100 parts by weight of the second acrylic polymer.
[0050] Furthermore, (c) the polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer is preferably at least one selected from the group consisting of polyalkylene glycol mono(meth)acrylate, methoxypolyalkylene glycol (meth)acrylate, and ethoxypolyalkylene glycol (meth)acrylate, in an amount of 1 to 50 parts by weight, more preferably 1 to 40 parts by weight, and particularly preferably 1 to 30 parts by weight, per 100 parts by weight of the second acrylic polymer. In addition, it is preferable that the ratio of the total of (c) at least one or more polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomers is 1 to 30 parts by weight per 100 parts by weight of (a) at least one or more (meth)acrylic acid ester monomers having an alkyl group carbon number of C1 to C18.
[0051] The monomer other than the (c) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer to be copolymerized into the second acrylic polymer may be at least one of the above-mentioned (a) (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C18 and (b) copolymerizable monomer containing a hydroxyl group. The monomers (a) and (b) to be copolymerized into the second acrylic polymer may be different from the monomers (A) and (B) to be copolymerized into the first acrylic polymer. The second acrylic polymer may not be copolymerized with a copolymerizable monomer containing a carboxyl group.
[0052] The method for producing the acrylic polymer contained in the pressure-sensitive adhesive composition according to the present embodiment is not particularly limited, and any known polymerization method such as solution polymerization or emulsion polymerization can be used. The weight average molecular weight of the copolymer of the first acrylic polymer is, for example, more than 300,000 and 1,200,000 or less. The weight average molecular weight of the copolymer of the second acrylic polymer is, for example, more than 300,000 and 1,000,000 or less, preferably more than 300,000 and 800,000 or less, and more preferably more than 400,000 and 800,000 or less. If the weight average molecular weight of the copolymer of the second acrylic polymer is less than 300,000, the stain resistance of the polarizing plate is deteriorated, which is undesirable.
[0053] The acid value of the first acrylic polymer is preferably 0.1 to 1.0. This can improve the stain resistance. Here, the "acid value" is an index representing the acid content, and is expressed as the number of milligrams of potassium hydroxide required to neutralize 1 g of a polymer containing a carboxyl group. The acid value of the second acrylic polymer is preferably 1.0 or less, and may be 0.0 when no copolymerizable monomer containing a carboxyl group is copolymerized with the second acrylic polymer.
[0054] The pressure-sensitive adhesive composition according to the present embodiment contains an antistatic agent (G). The antistatic agent (G) according to the present embodiment is an ionic compound consisting of a cation and an anion, the anion having a number of fluorine atoms of F7 or more. This ionic compound preferably has a melting point of 25 to 50°C and is solid at room temperature (e.g., 25°C). The ionic compound is preferably contained in an amount of 0.01 to 15 parts by weight, more preferably 0.01 to 10 parts by weight, and particularly preferably 0.01 to 8 parts by weight, per 100 parts by weight of the first acrylic polymer.
[0055] The anion of the ionic compound is C6F5(CF2) n COO - , C6F5(CF2) n SO3 - , C6F5(CF2) n O - , C6F5O(CF2) n SO3 - , (C6F5CO)2N - , (C6F5CO)3C - , (C6F5SO2)2N - , (C6F5SO2)3C - , (C6F5OSO2)2N - , (C6F5OSO2)3C - , (C6F5)4B - , CF3(CF2)3SO3 - In the above, n is an integer of 1 or more. Examples of the cation of the ionic compound include at least one selected from the group consisting of pyridinium, imidazolium, phosphonium, sulfonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylium, lithium, and morpholinium.
[0056] Specific examples of the (G) antistatic agent include methyltrioctylammonium tris(pentafluorobenzenesulfonyl)methide salt, 3-methyl-1-octylpyridinium nonafluorobutanesulfonate salt, 1-ethyl-3-methylimidazolium tetrakispentafluorophenylborate salt, and 1-butyl-1-methylpiperidinium bis(pentafluorobenzenesulfonyl)imide salt.
[0057] The pressure-sensitive adhesive composition according to the present embodiment further contains (D) a trifunctional or higher isocyanate compound as a crosslinking agent. Examples of the trifunctional or higher isocyanate compound (D) include biuret modified or isocyanurate modified diisocyanates such as hexamethylene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, tolylene diisocyanate, xylylene diisocyanate, etc., and adducts with trivalent or higher polyols such as trimethylolpropane and glycerin. The ratio of the trifunctional or higher isocyanate compound (D) is, for example, 0.01 to 5 parts by weight relative to 100 parts by weight of the first acrylic polymer.
[0058] The pressure-sensitive adhesive composition according to the present embodiment may contain a crosslinking retarder (E). Examples of the crosslinking retarder (E) include β-ketoesters such as methyl acetoacetate, ethyl acetoacetate, octyl acetoacetate, oleyl acetoacetate, lauryl acetoacetate, and stearyl acetoacetate, and β-diketones such as acetylacetone, 2,4-hexanedione, and benzoylacetone. These are ketoenol tautomer compounds, and in a pressure-sensitive adhesive composition using a polyisocyanate compound as a crosslinking agent, blocking the isocyanate group of the crosslinking agent can suppress excessive viscosity increase and gelation of the pressure-sensitive adhesive composition after the crosslinking agent is added, thereby extending the pot life of the pressure-sensitive adhesive composition. The crosslinking retarder (E) is preferably a ketoenol tautomer compound, and is preferably at least one selected from the group of compounds consisting of acetylacetone and ethyl acetoacetate. The crosslinking retarder (E) is preferably contained in a ratio of 0.1 to 300 parts by weight per 100 parts by weight of the first acrylic polymer.
[0059] The pressure-sensitive adhesive composition according to the present embodiment may contain a crosslinking catalyst other than a tin compound as the crosslinking catalyst (F). The crosslinking catalyst (F) may be any substance that functions as a catalyst for the reaction (crosslinking reaction) between the copolymer and the crosslinking agent when the crosslinking agent is a polyisocyanate compound. Examples of crosslinking catalysts other than tin compounds include amine compounds such as tertiary amines, metal chelate compounds, organolead compounds, organozinc compounds, and other organometallic compounds.
[0060] The metal chelate compound of the (F) crosslinking catalyst is a compound in which one or more polydentate ligands L are bonded to a central metal atom M. The metal chelate compound may or may not have one or more monodentate ligands X bonded to the metal atom M. Specific examples of the metal chelate compound include tris(2,4-pentanedionato)iron(III), iron trisacetylacetonate, titanium trisacetylacetonate, ruthenium trisacetylacetonate, zinc bisacetylacetonate, aluminum trisacetylacetonate, zirconium tetrakisacetylacetonate, tris(2,4-hexanedionato)iron(III), bis(2,4-hexanedionato)zinc, tris(2,4-hexanedionato)titanium, tris(2,4-hexanedionato)aluminum, and tetrakis(2,4-hexanedionato)zirconium.
[0061] The crosslinking catalyst (F) is preferably at least one metal chelate compound selected from the group consisting of aluminum chelate compounds, titanium chelate compounds, and iron chelate compounds, and is preferably contained in an amount of 0.001 to 0.5 parts by weight based on 100 parts by weight of the first acrylic polymer.
[0062] Since the crosslinking retarder (E) has an effect of suppressing crosslinking in contrast to the crosslinking catalyst (F), it is preferable to appropriately set the ratio of the crosslinking retarder (E) to the crosslinking catalyst (F). In order to extend the pot life of the pressure-sensitive adhesive composition and improve storage stability, the weight ratio of (E) / (F) is preferably 80 to 1000. Here, the weight ratio of (E) / (F) is the quotient value obtained by dividing the weight parts of (E) by the weight parts of (F).
[0063] The pressure-sensitive adhesive composition according to the present embodiment may contain, as an optional component, (H) a polyether-modified siloxane compound. (H) The polyether-modified siloxane compound is a siloxane compound having a polyether group, and has a general siloxane unit [-SiR 1 2-O-], as well as siloxane units with polyether groups [-SiR 1(R 2 O(R 3 O) n R 4 )-O-], where R 1 is one or more alkyl or aryl groups, R 2 and R 3 is one or more alkylene groups, R 4 indicates one or more alkyl or acyl groups (terminal groups). The polyether group is a polyoxyethylene group [(C2H4O) n 〕 and polyoxypropylene group〔(C3H6O) n In the siloxane unit having a polyether group, the terminal of the polyether group is an OH group (R 4 =H).
[0064] The polyether-modified siloxane compound (H) is preferably a polyether-modified siloxane compound having an HLB value of 6 to 12. The polyether-modified siloxane compound (H) is preferably contained in an amount of 0.01 to 0.5 parts by weight, more preferably 0.02 to 0.35 parts by weight, and particularly preferably 0.02 to 0.25 parts by weight, per 100 parts by weight of the first acrylic polymer. The HLB value is the hydrophilic-lipophilic balance (hydrophilic-lipophilic ratio) as defined in, for example, JIS K3211 (surfactant terminology) or the like.
[0065] Polyether-modified siloxane compounds can be obtained, for example, by grafting an organic compound having an unsaturated bond and a polyoxyalkylene group onto a polyorganosiloxane main chain having a silicon hydride group by a hydrosilylation reaction.Specific examples include dimethylsiloxane-methyl(polyoxyethylene)siloxane copolymer, dimethylsiloxane-methyl(polyoxyethylene)siloxane-methyl(polyoxypropylene)siloxane copolymer, and dimethylsiloxane-methyl(polyoxypropylene)siloxane polymer.
[0066] By blending the (H) polyether-modified siloxane compound in the pressure-sensitive adhesive composition, the adhesive strength and rework performance of the pressure-sensitive adhesive layer can be improved. The weight-average molecular weight of the (H) polyether-modified siloxane compound is preferably 10,000 or less. From the viewpoint of compatibility with the first acrylic polymer, the lower the HLB value and the lower the molecular weight, the better the compatibility. However, if the polyether-modified siloxane compound has a low molecular weight, even if it has a relatively high HLB value and slightly low compatibility with the polymer, excellent antistatic properties can be obtained.
[0067] The adhesive composition of the present embodiment may contain, as appropriate, known additives such as surfactants, curing accelerators, plasticizers, fillers, curing retarders, processing aids, antioxidants, antioxidants, etc. These may be used alone or in combination of two or more kinds.
[0068] The pressure-sensitive adhesive composition of the present embodiment is suitable as a pressure-sensitive adhesive composition for a surface protection film to be attached to the protective layer of the polarizer of a polarizing plate. Here, the protective layer of the polarizer of the polarizing plate is at least one selected from the group consisting of a TAC-based film, a PMMA-based film, and a PET-based film. Here, TAC is an abbreviation for triacetyl cellulose, PMMA is an abbreviation for polymethyl methacrylate, and PET is an abbreviation for polyethylene terephthalate. The pressure-sensitive adhesive composition of the present embodiment may be usable for three or more types of surface substrates consisting of TAC, PMMA, and PET by the same pressure-sensitive adhesive layer.
[0069] The surface treatment applied to the surface of the protective layer of the polarizer of the polarizing plate may be at least one selected from the group consisting of untreated, AG treatment, LR treatment, AR treatment, AG-LR treatment, and AG-AR treatment. Here, AG stands for anti-glare, LR stands for low reflection, and AR stands for anti-reflection. The pressure-sensitive adhesive composition of the present embodiment can improve the stain resistance of at least one of adherends that have been treated with AG, LR, AR, AG-LR, or AG-AR, when the substrate of the surface of the polarizing plate is PMMA or PET.
[0070] The pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition of the present embodiment has a surface resistivity of 1.0×10 +12 It is preferable that the resistance is 5.0×10 +11 It is more preferable that the resistance is 1.0×10 +11 It is particularly preferable that the surface resistivity is Ω / □ or less. If the surface resistivity is high, the performance of dissipating static electricity generated when peeling the adhesive layer from the adherend is poor. Therefore, by making the surface resistivity sufficiently small, the peeling electrification voltage caused by static electricity generated when peeling the adhesive layer from the adherend is reduced, and the influence on the adherend can be suppressed.
[0071] The adhesive layer obtained by crosslinking the adhesive composition of the present embodiment preferably has a peeling electrification voltage in the range of -0.3 to +0.3 kV with respect to a low refractive index layer formed on the adhesion surface using a composition for forming a low refractive index layer containing a fluorine compound. Examples of the fluorine compound used in the composition for forming a low refractive index layer include fluorine-containing copolymers which are polymers of one or more of fluorinated olefins, fluorinated vinyl ethers, fluorinated alkyl (meth)acrylates, etc., and condensates of fluorinated alkyl group-containing silane compounds. The fluorine-containing copolymer may be copolymerized with non-fluorinated monomers such as olefins, vinyl ethers, and (meth)acrylates in addition to fluorinated monomers. The low refractive index layer may be combined with a high refractive index layer or the like to form an antireflection layer.
[0072] The adhesive layer obtained by crosslinking the adhesive composition of the present embodiment has an adhesive strength of 0.04 to 0.2 N / 25 mm at a low peeling speed of 0.3 m / min, preferably 2.0 N / 25 mm or less at a high peeling speed of 30 m / min, and more preferably 0.2 to 1.6 N / 25 mm at a high peeling speed of 30 m / min. This allows the adhesive strength to have little change depending on the peeling speed, and allows for rapid peeling even at high-speed peeling. In addition, when the surface protective film is peeled off once for re-adhesion, excessive force is not required, and it is easy to peel off from the adherend.
[0073] The gel fraction of the pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition of the present embodiment is preferably 95 to 100%, more preferably 97 to 100%. With such a high gel fraction, the adhesive strength is not excessively high at a low peel speed, the elution of unpolymerized monomers or oligomers from the copolymer is reduced, reworkability and durability at high temperatures and high humidity are improved, and contamination of the adherend can be suppressed.
[0074] The adhesive film of the present embodiment is formed by forming an adhesive layer crosslinked from the adhesive composition of the present embodiment on one side or both sides of a resin film. The surface protection film of the present embodiment is formed by forming an adhesive layer crosslinked from the adhesive composition of the present embodiment on one side of a resin film. The adhesive composition of the present embodiment has excellent antistatic performance, has an excellent balance of adhesive strength at low and high peeling speeds, and also has stain resistance. Therefore, it can be suitably used as a surface protection film for a polarizing plate.
[0075] As the base film of the pressure-sensitive adhesive layer and the release film (separator) that protects the adhesive surface, a resin film such as a polyester film can be used. One side of the resin film may be subjected to antistatic treatment and antifouling treatment on the side opposite to the side on which the pressure-sensitive adhesive layer is formed. Antistatic treatment may include coating or kneading of an antistatic agent. Antifouling treatment may include treatment with a silicone-based or fluorine-based release agent or coating agent, silica fine particles, etc. The release film may be subjected to release treatment with a silicone-based, fluorine-based, or long-chain alkyl-based release agent on the side that is to be joined to the adhesive surface of the pressure-sensitive adhesive layer.
[0076] In addition, an optical film with a pressure-sensitive adhesive layer can be obtained by laminating a pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition of the present embodiment on at least one surface of an optical film. Examples of optical films include polarizing films, retardation films, anti-reflection films, anti-glare films, ultraviolet absorbing films, infrared absorbing films, optical compensation films, and brightness enhancing films. Examples of devices to which optical members are applied include liquid crystal panels, organic EL panels, and touch panels. In the case of optical surface protection films such as surface protection films for polarizing plates and pressure-sensitive adhesive films, the base film and pressure-sensitive adhesive layer preferably have sufficient transparency. EXAMPLES
[0077] The present invention will now be described in detail with reference to examples.
[0078] <Production of First Acrylic Polymer> [Example 1] Nitrogen gas was introduced into a reactor equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, and the air in the reactor was replaced with nitrogen gas. Then, 90 parts by weight of 2-ethylhexyl acrylate, 10 parts by weight of methyl acrylate, 5.5 parts by weight of 8-hydroxyoctyl acrylate, 0.2 parts by weight of acrylic acid, and a solvent (ethyl acetate) were added to the reactor. Then, 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator was dropped over 2 hours, and the mixture was reacted at 65°C for 6 hours to obtain a first acrylic polymer used in Example 1. [Examples 2 to 6 and Comparative Examples 1 to 3] The first acrylic polymer solutions used in Examples 2 to 6 and Comparative Examples 1 to 3 were obtained in the same manner as the first acrylic polymer solution used in Example 1 above, except that the monomer compositions were as shown in Table 1 (A) to (C), respectively.
[0079] <Production of Pressure-Sensitive Adhesive Composition and Surface Protective Film> [Example 1] To the first acrylic polymer solution of Example 1 produced as described above, 2.0 parts by weight of a crosslinking agent (Coronate HX), 9 parts by weight of a crosslinking retarder (acetylacetone), 0.1 parts by weight of a crosslinking catalyst (titanium trisacetylacetonate), 0.9 parts by weight of an antistatic agent (methyltrioctylammonium tris(pentafluorobenzenesulfonyl)methide salt), 0.05 parts by weight of a polyether-modified siloxane compound (HLB=7), and 0.2 parts by weight of a copolymer B-1 (molecular weight 600,000) were added and mixed with stirring to obtain a pressure-sensitive adhesive composition of Example 1. This pressure-sensitive adhesive composition was applied onto a release film (a silicone resin-coated PET film), and then dried at 90° C. to remove the solvent, thereby obtaining a pressure-sensitive adhesive layer having a thickness of 20 μm. Thereafter, the adhesive layer with a release film was transferred to the side of the base film (a PET film with one side treated for antistatic and antifouling) opposite the side treated for antistatic and antifouling, thereby obtaining the surface protection film of Example 1 having a laminate structure of "base film / adhesive layer / release film". [Examples 2 to 6 and Comparative Examples 1 to 3] The surface protection films of Examples 2 to 6 and Comparative Examples 1 to 3 were obtained in the same manner as the surface protection film of Example 1 above, except that the compositions of the additives were changed as shown in Table 1 for (D) to (H) and Copolymer B.
[0080] [Table 1]
[0081] In Table 1, the parts by weight of each component were calculated assuming that the total of (A) (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C18 is 100 parts by weight. Note that, although "I-2" in Comparative Example 2 is listed in the (A) column for convenience, it does not correspond to (A) (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C18. In Table 1, in each of the columns (D), (E), (F), (G), (H), and (Copolymer B), the content (parts by weight) of each component is shown by the numerical value in parentheses ( ), with the first acrylic polymer being 100 parts by weight.
[0082] The compound names of the abbreviations of each component used in Table 1 are shown in Tables 2 and 3. The second acrylic polymer in the above embodiment is "copolymer B", and the meanings of the abbreviations of its component monomers (a), (b), and (c) are described in (A), (B), and (I), respectively. Coronate (registered trademark) HX, HL, and L are product names of Tosoh Corporation, and Takenate (registered trademark) D-140N is a product name of Mitsui Chemicals, Inc.
[0083] [Table 2]
[0084] [Table 3]
[0085] Among the (G) antistatic agents, G-1 to G-4 are all ionic compounds having an anion with the number of fluorine atoms being F7 or more, and having a melting point of 25° C. or more and being solid. G-5 is an ionic compound having an anion with the number of fluorine atoms being F5, and having a melting point of 25° C. or more and being solid. Of the (H) polyether-modified siloxane compounds, H-1 to H-6 all have a weight average molecular weight of 10,000 or less. Among (I) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomers, I-1 to I-3 have a diester content of 0.2% or less in the monomer, and I-4 has a diester content of 0.8% in the monomer. In addition, n in the column for group (I) in Table 3 is a number indicating the average repeat number of alkylene oxide.
[0086] <Test methods and evaluation> The surface protection films of Examples 1 to 6 and Comparative Examples 1 to 3 were each aged for 7 days in an atmosphere of 23° C. and 50% RH, and then evaluated by the following test methods.
[0087] <Adhesive strength test method> The release film was peeled off to expose the adhesive layer, and the surface protection film was attached to the surface of a polarizing plate via the adhesive layer, and after leaving it for one day, it was autoclaved at 50°C and 5 atm for 20 minutes and left at room temperature for another 12 hours to prepare a sample for measuring adhesive strength. The obtained sample was peeled off in the 180° direction at a low speed (0.3 m / min) or a high speed (30 m / min) using a tensile tester, and the peel strength was measured and used as the adhesive strength. Here, the protective layer of the polarizer of the polarizing plate is one selected from the group consisting of triacetyl cellulose (TAC), polymethyl methacrylate (PMMA), and polyethylene terephthalate (PET). In the LR polarizing plate and the AG-LR polarizing plate, the surface of the protective layer of the polarizer of the polarizing plate is subjected to a low reflection surface treatment with a composition containing a fluorine compound.
[0088] <Surface resistivity test method> After aging the surface protection film and before bonding to a polarizing plate, the release film was peeled off to expose the adhesive layer, and the surface resistivity of the adhesive layer was measured using a resistivity meter Hiresta UP-HT450 (manufactured by Mitsubishi Chemical Analytech).
[0089] <Test method for peeling electrification voltage> The release film was peeled off to expose the pressure-sensitive adhesive layer, and the surface protection film was attached to a polarizing plate having a low refractive index layer formed on the adhesion surface using a composition for forming a low refractive index layer containing a fluorine compound. When the surface protection film was peeled off at 180° at a pulling speed of 30 m / min, the voltage (charged voltage) generated by the adhesion body being charged was measured using high-precision static electricity sensors SK-035 and SK-200 (manufactured by Keyence Corporation), and the maximum measured value was taken as the peeling charged voltage.
[0090] <Test method for stain resistance> Each polarizing plate selected from the five types shown in Table 4 was attached to one side of a glass plate via an adhesive layer (double-sided adhesive tape) using a laminator. Then, a surface protection film was attached to the surface of each polarizing plate using a laminator. After storage for 3 days and 30 days in an environment of 23°C and 50% RH, the surface protection film was peeled off and the contamination state of the polarizing plate surface was visually observed. The criteria for judging the contamination resistance were as follows: no contamination on the surface of each polarizing plate was evaluated as "○", slight contamination was evaluated as "△", and contamination was evaluated as "×".
[0091] Table 4 shows the evaluation results for the surface protection films in Examples 1 to 6 and Comparative Examples 1 to 3. "Surface resistivity" is expressed as "m×10 +n " is expressed as "mE+n" (where m is any real value and n is a positive integer). The "Stain resistance (surface substrate / surface treatment)" column shows the evaluation results for each material and surface treatment of the surface substrate (protective layer of the polarizer) of five types of polarizing plates. "Plain" in "surface treatment" means untreated.
[0092] [Table 4]
[0093] The surface protection films of Examples 1 to 6 had an adhesive strength of 0.04 to 0.2 N / 25 mm at a slow peel speed of 0.3 m / min to a polarizing plate as an adherend, and an adhesive strength of 2.0 N / 25 mm or less at a fast peel speed of 30 m / min, demonstrating excellent adhesive performance. In addition, the surface protective films of Examples 1 to 6 had a surface resistivity of the pressure-sensitive adhesive layer of 1.0×10 +12 The peeling charge voltage of the adhesive layer against a low refractive index layer formed using a composition for forming a low refractive index layer containing a fluorine compound on the adhesion surface was within the range of -0.3 to +0.3 kV, indicating excellent antistatic performance. Furthermore, the surface protective films of Examples 1 to 6 did not stain the adherend, the polarizing plate, even after storage for 3 days and 30 days, and were also excellent in stain resistance. That is, the evaluation results shown in Table 4 for the surface protection films of Examples 1 to 6 demonstrate that the problems of the present invention were solved.
[0094] In the pressure-sensitive adhesive composition of Comparative Example 1, the weight-average molecular weight of copolymer B-5 is as small as 10,000. In addition, I-4 contained in copolymer B-5 has a high diester content of 0.8% and a high average repeat number n=23. In addition, the (b) component contained in copolymer B-5 of the second acrylic polymer is 3 parts by weight, which is less than the (B) component contained in the first acrylic polymer, 5.5 parts by weight. The surface protection film of Comparative Example 1 using such a pressure-sensitive adhesive composition has excellent stain resistance against polarizing plates using TAC as a base material, which has been used conventionally, but has slightly poor stain resistance against two types of polarizing plates using PMMA or PET as a base material.
[0095] In the pressure-sensitive adhesive composition of Comparative Example 2, a polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer is copolymerized with the first acrylic polymer, and the proportion of the copolymerizable monomer containing a hydroxyl group (B) is as high as 6.5 parts by weight. The surface protection film of Comparative Example 2 using such a pressure-sensitive adhesive composition had a low adhesive strength of 0.03 N / 25 mm at a low peel speed of 0.3 m / min, poor adhesive performance, and also poor stain resistance for two types of polarizing plate and slightly poor stain resistance for another type of polarizing plate.
[0096] In the pressure-sensitive adhesive composition of Comparative Example 3, the proportion of (C) the copolymerizable monomer containing a carboxyl group is high at 1.5 parts by weight, and the antistatic agent contains an anion having a number of fluorine atoms of F5 less than F7. The surface protection film of Comparative Example 3 using such a pressure-sensitive adhesive composition had a high peeling electrification voltage of 0.6 kV, poor antistatic performance, and also poor stain resistance for three types of polarizing plates and slightly poor stain resistance for another type of polarizing plate.
[0097] Thus, the surface protection films of Comparative Examples 1 to 3 could not solve the problems of the present invention. In addition, in the case of a surface protection film prepared in the same manner as in Example 1 except that it did not contain copolymer B, the surface resistivity was high and the peeling electrification voltage was high, resulting in poor antistatic performance and poor resistance to contamination of polarizing plates.
Claims
1. A pressure-sensitive adhesive composition comprising an acrylic polymer, an antistatic agent, and a crosslinking agent, the acrylic polymer being the following first acrylic polymer and second acrylic polymer: The first acrylic polymer is (A) at least one (meth)acrylic acid ester monomer having an alkyl group carbon number of C1 to C18, relative to a total of 100 parts by weight, (B) 1.0 to 6.0 parts by weight of at least one copolymerizable monomer containing a hydroxyl group; (C) 0.01 to 0.6 parts by weight of at least one copolymerizable monomer containing a carboxyl group; a first acrylic polymer which is a copolymer having an acid value of 0.1 to 1.0 and a weight average molecular weight of more than 300,000 and not more than 1,200,000, obtained by copolymerizing the above without containing a polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer; the first acrylic polymer contains 70 parts by weight or more of 2-ethylhexyl acrylate out of a total of 100 parts by weight of the at least one (meth)acrylic acid ester monomer (A) having an alkyl group with a carbon number of C1 to C18; The second acrylic polymer is (a) at least one (meth)acrylic acid ester monomer having an alkyl group with a carbon number of 1 to 18; (b) at least one copolymerizable monomer containing a hydroxyl group; (c) at least one polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer; a second acrylic polymer having a weight average molecular weight of more than 300,000 and not more than 800,000; the (c) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer has an average repeat number of alkylene oxides constituting the polyalkylene glycol chain of 3 to 14; the first acrylic polymer and the second acrylic polymer have a glass transition temperature of 0° C. or lower; the crosslinking agent is (D) a tri- or higher functional isocyanate compound, the antistatic agent is (G) an ionic compound having a melting point of 25 to 50° C., which is composed of a cation and an anion and has an anion in which the number of fluorine atoms is F7 or more; the cation of the ionic compound is one selected from the group consisting of pyridinium, imidazolium, phosphonium, sulfonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylium, lithium, and morpholinium; the pressure-sensitive adhesive composition contains the second acrylic polymer in a ratio of 0.1 to 5.0 parts by weight relative to 100 parts by weight of the first acrylic polymer, and contains (H) a polyether-modified siloxane compound in a ratio of 0.01 to 0.5 parts by weight relative to 100 parts by weight of the first acrylic polymer, and further contains (E) a crosslinking retarder and (F) a crosslinking catalyst other than a tin compound; The pressure-sensitive adhesive composition, wherein the polyether-modified siloxane compound (H) is a polyether-modified siloxane compound having an HLB value of 6 to 12.
2. The pressure-sensitive adhesive composition according to claim 1, which is for a surface protection film to be attached to a protective layer of a polarizer of a polarizing plate, wherein the protective layer of the polarizer of the polarizing plate is one type selected from the group consisting of a TAC-based film, a PMMA-based film, and a PET-based film, and the surface treatment applied to the surface of the protective layer of the polarizer of the polarizing plate is one type selected from the group consisting of untreated, AG treatment, LR treatment, AR treatment, AG-LR treatment, and AG-AR treatment.
3. The anion of the ionic compound is 6 F 5 (CF 2 ) n COO - , C 6 F 5 (CF 2 ) n SO 3 - , C 6 F 5 (CF 2 ) n O - , C 6 F 5 O (CF 2 ) n SO 3 - , (C 6 F 5 CO) 2 N - , (C 6 F 5 CO) 3 C - , (C 6 F 5 SO 2 ) 2 N - , (C 6 F 5 SO 2 ) 3 C - , (C 6 F 5 OSO 2 ) 2 N - , (C 6 F 5 OSO 2 ) 3 C - , (C 6 F 5 ) 4 B - , C.F. 3 (CF 2 ) 3 SO 3 - (wherein n is an integer of 1 or more), 3. The pressure-sensitive adhesive composition according to claim 1, wherein the ionic compound is contained in an amount of 0.01 to 15 parts by weight based on 100 parts by weight of the first acrylic polymer.
4. 4. A pressure-sensitive adhesive film comprising a resin film and a pressure-sensitive adhesive layer formed by crosslinking the pressure-sensitive adhesive composition according to claim 1 on one side of the resin film.
5. A surface protection film for a polarizing plate, comprising the pressure-sensitive adhesive film according to claim 4.
6. 4. An optical film with a pressure-sensitive adhesive layer, comprising an optical film and a pressure-sensitive adhesive layer formed by crosslinking the pressure-sensitive adhesive composition according to claim 1 laminated on at least one surface of the optical film.
Citation Information
Patent Citations
Pressure-sensitive adhesive
JP1988225677A
Surface protective film for liquid crystal display panel
JP1999070629A
Pressure sensitive adhesive for surface-protecting film, and film for surface protection
JP1999256111A
Pressure-sensitive adhesive composition and surface protective film using the same
JP2011122054A
Pressure sensitive adhesive sheet
JP2014024993A